An Evaluation of the Child Rights Information Network: Examining Information Management in a Global NGO - Halpin, Edward; Khan, Andrea; Reale, Daniela (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper relates to the conference program in the areas of access and international issues, providing a report on a funded research project undertaken in 2001 and 2002. The research project examined some of the challenges of managing increasing information flows in the child rights community, and represented a partnership between the Leeds Metropolitan University and the. . .